Zinc Nanoparticles at Intercrystallite Sites of (Cu0.5Tl0.5)Ba2Ca3Cu4O12−δ Superconductor. (15th March 2016) - Qasim, Irfan; Mumtaz, M.; Nadeem, K.; Abbas, S. Qamar
Abstract : We synthesizedZ n x /(Cu0.5 Tl0.5 )Ba2 Ca3 Cu4 O 12 - δ Z n x /CuTl-1234 ( x = 0 3 wt.%) nanoparticles-superconductor composites by solid-state reaction technique and examined the effects of zinc (Zn) nanoparticles on structural and superconducting properties of CuTl-1234 phase. Unaltered crystal structure of host CuTl-1234 phase confirmed the existence of Zn nanoparticles at intercrystallite sites. We observed an improvement in grains size and intergrains connectivity by healing up the voids after incorporation of Zn nanoparticles in CuTl-1234 superconductor. Superconducting properties ofZ n x /CuTl-1234 composites were suppressed for all Zn nanoparticles concentrations. Suppression of zero resistivity critical temperature T c ( 0 ) and variation in normal state resistivity ρ 300 K (Ω-cm) were attributed to reduction of superconducting volume fractions and enhanced scattering cross section of mobile carriers.